1998
DOI: 10.1128/mcb.18.5.2640
|View full text |Cite
|
Sign up to set email alerts
|

The N-Terminal Domain of IκBα Masks the Nuclear Localization Signal(s) of p50 and c-Rel Homodimers

Abstract: Members of theTranscription factors of the Rel/NF-B family are present in most or all mammalian and avian cells and influence the expression of many genes (for a review, see references 1 and 19). These factors are related to each other over a region of about 300 amino acids called the Rel Homology Domain (RHD), which governs DNA binding and dimerization. Although each protein has a nuclear localization signal (NLS), the various homo-and heterodimers are cytoplasmic by virtue of an inhibitor protein whose bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
0
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 31 publications
5
47
0
3
Order By: Relevance
“…fibroblast growth factor 3) (41). Examples of NLS "masking" by structural alterations and/or other cellular proteins, a prime example being the transcription factor NF-B/Rel bound by its inhibitor IB are known (42). The data herein could be consistent with some sort of unmasking of an NLS to gain nuclear entry and also do not rule out the possibility that 5-lipoxygenase is "piggybacked" to the nucleus by some other chaperone protein.…”
Section: -Lipoxygenase Nuclear Localizationsupporting
confidence: 75%
“…fibroblast growth factor 3) (41). Examples of NLS "masking" by structural alterations and/or other cellular proteins, a prime example being the transcription factor NF-B/Rel bound by its inhibitor IB are known (42). The data herein could be consistent with some sort of unmasking of an NLS to gain nuclear entry and also do not rule out the possibility that 5-lipoxygenase is "piggybacked" to the nucleus by some other chaperone protein.…”
Section: -Lipoxygenase Nuclear Localizationsupporting
confidence: 75%
“…Two distinct but not exclusive mechanisms have been proposed to account for the cytoplasmic retention of IB␣/NF-B complexes: (i) an active nuclear export mediated by the N-terminal NES promotes continuous export from the nucleus and (ii) the N-terminal region of IB␣ is thought to mask the p50 NLS either directly or indirectly. These dual functions of the N-terminal region are mediated by the same sequence located between residues 45 and 54, but differences are observed in the nature of residues essential for each function (42)(43)(44)58). Data reported here indicate that the same N-terminal domain (residues 37-55) displays properties of a CRS that promotes anchoring of IB␣ in the cytoplasm and on the outer membrane of the nuclear envelope.…”
Section: Discussionmentioning
confidence: 63%
“…It has been recently reported that an NES located in the N-terminal domain of IB␣ (which was not in the NF-B/IB␣ structure) participates to the cytoplasmic localization of inactive NF-B/IB␣ complexes (43,44) by inducing an efficient export of the complex out of the nucleus. In addition, the N-terminal region of IB␣ has also been proposed to directly or indirectly affect the p50 NLS accessibility and function, thus limiting nuclear import of NF-B/IB␣ complexes (43,58).…”
mentioning
confidence: 99%
“…In the resting cell, the heterodimer generates a ternary complex with a member of the I B family of inhibitory proteins. I B binding sterically hinders a nuclear localization site, and consequently, the complex is retained in the cytosol (20,24). Following cellular stimulation by a wide array of activators, such as cytokines (tumor necrosis factor alpha and interleukin 1, for example), viral and bacterial products, UV light, and oxidants, specific I B kinases that phosphorylate the protein on two specific Ser residues, 32 and 36 (8), are activated (30,41,43).…”
mentioning
confidence: 99%